Advancing remission in severe asthma with Benralizumab: latest findings, current perspectives and future direction - Louis, Renaud; Lommatzsch, Marek; Jackson, David J.; Menzies-Gow, Andrew; Shavit, Anat; Cohen, David; Hoyte, Flavia C. L.; Korn, Stephanie (Clinical & experimental allergy, 2025)
The introduction of biologics, such as benralizumab (an anti-IL-5 receptor α humanised monoclonal antibody), has made remission a feasible goal for patients with severe eosinophilic asthma (SEA). However, there are remaining research gaps and no clear consensus on the definition of remission. We consolidated post hoc remission data from clinical trials and real-world studies of benralizumab in patients with SEA to gather insights on: testing different definitions; predictors of remission; the effect of comorbidities on achieving remission; remission and background medication reduction; long-term remission patterns with benralizumab; and remission in a real-life setting. In the SIROCCO and CALIMA Phase 3 randomised studies, patients with remission had higher baseline median blood eosinophil counts, were more likely to have a FEV1 of ≥ 65% predicted, had fewer exacerbations within 12 months and had lower mean ACQ-6 scores. Compared with the overall population, patients with a history of nasal polyps were also more likely to achieve remission with benralizumab. Analyses of the BORA and MELTEMI extension studies showed that in the longer term, once remission is achieved with benralizumab, patients are likely to remain in remission with continued treatment. In the open-label, single-arm ANDHI-In Practice and PONENTE studies, patients achieving remission had a shorter median time since asthma diagnosis, higher median age at asthma onset and lower median ACQ-6 scores. The SHAMAL study and the Phase 3b ANDHI-In Practice substudy demonstrate that remission is maintained with benralizumab even when patients reduce their background medication. Finally, the XALOC-1 real-world study highlights how patients with lower BMI are more likely to achieve remission with benralizumab. These findings demonstrate that achieving remission in patients with SEA is feasible with benralizumab and, in turn, inform future directions for research and treatment that includes a promising shift towards a new era of treat-to-target. This manuscript was supported by AstraZeneca, the manufacturer of benralizumab.